Drive To Fulfill Father's Commands In Martin Scorsese's Hugo Movie (2011): An Individual Psychological Approach - Haningrum, Nur Hajah, Dr. Phil. Dewi Candraningrum. S.Pd., M.Ed, Drs. H. Abdillah Nugroho, M. Hum (2013)
The major problem of this study is to reveal how is Hugo's drive to fulfill father's commands in Hugo movie. The objective of this study is to analyze the movie based on it's structural elements and an individual psychological approach. In analysis, the writer uses descriptive qualitative method. The object of this study is Hugo directed by Martin Scorsese. The data sources are primary and secondary data sources. The primary data source is Hugo movie itself and the secondary data sources are the other sources related to the primary data such as information about director's biography, websites, and the other sources such a book related to the individual psychological approach by Alfred Adler. The technique of the data collection are watching the movie repeatedly, taking note the important part, arranging the data into several groups, selecting particular parts that is important and relevant for analysis, drawing conclusion, educational implication, and formulate it's suggestion. The technique of data analysis is descriptive analysis. The result of this study is presented in the following conclusions. First, Martin Scorsese wants to describe that the hard effort is the process to achieve human's dream. He wants to show that people can achieve their dream with effort and never gives up . Second, based on individual psychological analysis, Martin Scorsese wants to reflect Hugo's drive to fulfill father's commands that can produce happiness.